AN ANALYSIS OF CODE SWITCHING BY THE ENGLISH TEACHERS IN THE CLASSROOM AT SMA DARMA YUDHA PEKANBARU - Prakas Prabowo; Jismulatif '; Dahnilsyah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive qualitative research was aimed to know the frequency of types and functions of code switching by the English teachers in the classroom at SMA Darma Yudha Pekanbaru. The sample of the research was consisted of three English teachers. In order to gather the data, the writer used observation, recorder and students’ questionnaire to support the data. The types of code switching appearing in the classroom were observed based on the theory proposed by Poplack, while the functions of code switching appearing in the classroom were observed based on the theory proposed by Matton and Burenhult. Moreover, to interpret the data gathered, the writer analyzed them through four steps of analysis, they are: recording, rechecking, transcribing and classifying the data. While in the students’ questionnaire, the responses were analyzed through simple percentage calculation. The findings indicate that the types of code switching were simply found in three types: (a) thirty seven times in intra-sentential code switching, (b) thirty six times in inter-sentential code switching and (c) fifteen times in tag switching. Moreover, the functions of code switching used by the English teachers in the classroom were found in four functions; (a) twenty one times in elaboration function, (b) twelve times in affective function, (c) sixteen times in repetitive function and (d) six times addressee specification. Finally, the results of students’ questionnaire indicate that the students had a positive perception of teachers’ code switching in the English instructional process.Keywords: Code Switching, English instructional process.